Pelatihan Pembuatan Program Latihan Cabang Olahraga Futsal pada Pelatih Kota Jayapura (Indonesian Version) - Tri Setyo Guntoro; Saharuddin Ita; Ansar CS; Syahruddin Syahruddin; Ipa Sari Kardi; Muh Syaiful Syam (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2025)
Training programs are very important for futsal coaches to achieve goals and maximize the team's potential. Through training programs, coaches can design effective training sessions to develop individual and team skills and develop appropriate playing strategies. The main problem faced is a lack of understanding of exercise programs and skills in creating effective exercise programs. This training involved 37 participants and used a structured method, including pretest, education, theoretical and practical training, mentoring, posttest and evaluation. The aim of the activity is to increase participants' knowledge and skills in designing futsal training programs that are effective and suit the needs of athletes. The training results showed a significant increase based on pretest and posttest data, the percentage of participants who understood the training program increased from 40.5% to 94.6%. Improving the quality of futsal coaching in Jayapura City is expected to improve athlete performance and advance the development of futsal sports in Jayapura City.